The Impact of Science Curricula on Climate Change Mitigation in Saudi Arabia: A Sustainable Development Perspective - A. AlGhamdi, Reem (Journal of Ecohumanism, 2025)
This study aimed to explore the role of science curricula in reducing climate change in light of the dimensions of sustainable development in KSA. The study employed the descriptive analytical method to analyze science textbooks of the three-grade intermediate stage (2023-2024). The study utilized a content analysis sheet based on an indicator framework designed to assess the role of these curricula in reducing climate change. The study results revealed that the science textbooks of the intermediate stage in KSA show a limited role in addressing climate change within the context of sustainable development dimensions. The overall presence of indicators related to climate change reductions was found to be very low (10.1%). The distribution of these indicators is as follows: changes in the economy and production (29.4%), changes in the environment and atmosphere (27.2%), changes in occupational safety and security standards (16.2%), changes in the Earth’s crust, seas, and oceans (15.4%), and changes in health and social responsibility (11.8%). Most of the indicators were included implicitly within subtopics rather than being treated as core topics. Many key issues were largely neglected such as air pollution, global warming, water pollution, oil spills, fossil fuel combustion, radioactive leakage, and the disruption of ocean currents. The study recommended conducting a systematic review of the content and activities of the intermediate-stage science textbooks in KSA.